Analisis Persepsi Konsumen terhadap Kualitas Pelayanan Tori Coffee di Kabupaten Toraja Utara - Dandi Saputra; Dina Ramba; Yohanis Lotong Ta’dung (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Analysis of Consumer Service Perceptions of Services of Tori Coffe Service Quality In North Toraja District. This study aims to determine Customer Service Perceptions of Services at Tori Coffe North Toraja. This study The object of this study was Tori Coffe using a quantitative approach with simple linear regression analysis, to test and prove the research hypothesis using the SPSS version 26 application. The population in this study were 150 respondents and a sample of 69 respondents Tori Coffe North Toraja Regency. This study shows that the perception of customer service at Tori Coffe North Toraja is in the sufficient category where as many as 24 consumers (34.78%) are respondents. This means that the quality of service provided by Tori Coffe has fulfilled the wishes of the consumer.